Il dibattito sulla Protezione Sociale Globale e Transnazionale: Introduzione - Castellani, S. (2019)
The Welfare State, consolidated along the XX century as the model of social protection within the neo-liberal societies, has been increasingly questioned. The last economic recession has contributed to a further deterioration of Welfare State and social risks have become stronger for a growing part of population. Particularly, many migrants remain on the edges of the traditional social protection systems because of their job status or their residence / citizenship status. Reflecting on these premises, some scholars stress the need of thinking about a configuration of social protection that crosses the national borders and propose to analyse how people who live transnationally are restructuring their protection in order to face social risks. This Special Issue aims to introduce the debate on the Global and Transnational Social Protection within the Italian migration studies. It starts from the state of the art and give example of original empirical studies carried out in this scientific line in Italy, Spain, Austria and UK